2007
DOI: 10.1007/s10620-007-9891-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcome of Chronic Viral Hepatitis with Acute Exacerbation in Patients with Concurrent Infections of Hepatitis B and C Virus

Abstract: Virus interference existed in chronic hepatitis with acute exacerbation patients with concurrent HBV and HCV infections. Clinical outcome for patients positive for serum HBVDNA was much worse than those negative for serum HBVDNA. When chronic hepatitis with acute exacerbation occurs in patients with concurrent HBV and HCV infection, aggressive management should be investigated and antiviral therapy targeting of HBV infection should be administered early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Samples obtained prior to ART initiation showed that triply infected patients had a trend toward lower HBV DNA levels, similar to other reports in HBV/HCV patients. [22][23][24] No difference in HCV RNA levels in the triply infected patients was observed when compared to the HIV/ HCV coinfected group; this result differs from a recent study. 24 Hepatitis D virus infection occurred more often in those with triple infection, suggesting that the intravenous/parenteral route is the most likely mode of transmission of these infections.…”
Section: Discussioncontrasting
confidence: 98%
“…Samples obtained prior to ART initiation showed that triply infected patients had a trend toward lower HBV DNA levels, similar to other reports in HBV/HCV patients. [22][23][24] No difference in HCV RNA levels in the triply infected patients was observed when compared to the HIV/ HCV coinfected group; this result differs from a recent study. 24 Hepatitis D virus infection occurred more often in those with triple infection, suggesting that the intravenous/parenteral route is the most likely mode of transmission of these infections.…”
Section: Discussioncontrasting
confidence: 98%
“…In the setting of active i.v drug abuse [1][2][3][4][5]8], and also in regions where the prevalence of chronic hepatitis by HBV, HDV and HCV is proportionally elevated or reincreasing [1][2][3][4][5], both co-infections and superinfections may occur, sometimes leading to a rapidly evolving liver failure responsible for organ transplantation and death, or late sequelae like cirrhosis or hepatocellular carcinoma [3][4][5][7][8][9]. Concurrently, other hepatotropic viruses like HGV are emerging [10], since laboratory diagnosis benefits from an excellent, endless progress [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…lobally, viral hepatitis accounts for a considerable burden of morbidity and mortality. Hepatitis B (HBV) and hepatitis C (HCV) are the most common causes of chronic liver disease in different regions 1 and the majority of cirrhosis and hepatocellular carcinoma has been attributed to either virus. 2 In 2002, 103,000 and 53,000 deaths worldwide were estimated to be directly caused by HBV and HCV, respectively.…”
mentioning
confidence: 99%
“…5 Among HCV-infected persons, 60-85% will develop chronic HCV infection. 6 Because HBV and HCV share common risk factors and routes of transmission, 1,7 co-infection is not uncommon. 8 Co-infection with two or more hepatitis viruses is associated with poorer outcomes and accelerated progression of liver disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation